Through the garden fence - Robins, Kathy (Michaelis School of Fine Art, 2016)
This project attempts to tie together different threads of my experience. It begins with the memory of looking through the garden fence and hedge of my childhood and considers the simultaneously separate and enmeshed lives of my immediate family and those outside of it. In this project I have engaged with the garden as a point of connection, a means by which to consider the possibility of more Edenic, sustainable futures rooted in concepts of care. An investigation into care, through my making, has been central to my research. Under the harsh structures of apartheid, the natural world carried on in spite of the social and environmental restrictions implemented by the apartheid government. I am interested primarily in human experiences of care, belonging and relationship against the backdrop of migrancy, the displacement of discarded people to infertile land, and the loss of indigenous cultures and natural areas. My intention in this work is for the viewer to be reminded of the unending cycles of nature - seasons, joy, nurturance and recurrence - in their silent yet peripatetic way. In this turning towards nature there is a recognition of the spiritual essence of the world as separate and distinct from humankind's inhumanity to each other. In a contemporary context, the prevalence of people from across Africa displaced into South Africa demands a closer consideration of human connections to the land, as does the recent crisis of Syrian migrants in Europe and the ensuing ethnic xenophobia. At present there are 60 million people displaced due to war, religious tension, politics and race. However, there is hope in the care provided by non-governmental organisations, the United Nations, governments and grassroots initiatives; people who want to help those with a bag and a child on their back.